R E V I E W: Species definition of procaryotes based on 16S rRNA and protein coding genes sequence - ARTINI PANGASTUTI (Society for Indonesian Biodiversity, 2006)
Until now it is complicated for demarcating species of prokaryotes. The 16S rRNA gene sequence provide phylogenetic basis for classification. It has been widely accepted that more than 97% similarity in 16S rRNA gene sequence is a species definition for prokaryotes. However, this criterion can not correspond to real ecological unit, thus can not reveal the functional diversity in nature. The interaction with the environment is defined at the level of functional genes, not 16S rRNA gene. Protein-coding genes sequence can be expected to disclose much previously unknown ecological population of prokaryotes. These are the genes that determine the role of the species. Sequence similarity in multiple protein-coding genes is recommended as a primary criterion for demarcating taxa. Â© 2006 Jurusan Biologi FMIPA UNS Surakarta Key words: species definition, 16S rRNA, procaryotes, systematics